Investigation of a Novel NTRK1 Variation Causing Congenital Insensitivity to Pain With Anhidrosis - Yang, Kai; Xu, Yi-Cheng; Hu, Hua-Ying; Li, Ya-Zhou; Li, Qian; Luan, Ying-Yi; Liu, Yan; Sun, Yong-Qing; Feng, Zhan-Ke; Yan, You-Sheng; Yin, Cheng-Hong (Frontiers in Genetics, 2021)
Background: Congenital insensitivity to pain with anhidrosis (CIPA), a rare autosomal recessive sensory neuropathy, was caused mainly by bi-allelic mutations in the NTRK1 gene. The pathogenesis of CIPA still needs further elucidation. Methods: Here, we recruited a CIPA case and introduced whole-exome sequencing (WES) to identify the causative variation. Subsequently, an in silico molecular dynamic(MD) analysis was performed to explore the intramolecular impact of the novel variant. Meanwhile, in vitro functional study on the novel variant from a metabolomic perspective was conducted via the liquid chromatography-mass spectrometry(LC-MS) approach, of which the result was verified by quantitative real-time PCR (qRT-PCR). Results: A novel compound heterozygous variation in NTRK1(NM_001012331) was detected, consisting of the c.851-33T>A and c.2242C>T(p.Arg748Trp) variants. MD results suggested that p.Arg748Trp could impact the molecular structure stability. Results of the LC-MS and metabolic pathway clustering indicated that the NTRK1Arg748Trp variant would significantly affect the purine metabolism in vitro. Further analysis showed that it induced the elevation of NT5C2 mRNA. Conclusion: The findings in this study extended the variation spectrum of NTRK1, provided evidence for counseling to the affected family, and offered potential clues and biomarkers to the pathogenesis of CIPA.